Associations between symptoms of temporomandibular disorders, quality of life and psychological states in Asian Military Personnel. (17th December 2018) - Tay, Koong Jiunn; Yap, Adrian U‐Jin; Wong, Johnny Chiew Meng; Tan, Keson Beng Choon; Allen, Patrick Finbarr
Summary: Background: Symptoms of Temporomandibular Disorders (TMD) could affect oral health‐related quality of life (OHRQoL) and psychological distress. Objective: This study aims to determine the prevalence of TMD symptoms, and impact of type and number of TMD symptoms on OHRQoL and psychological states among Asian military personnel. Method: The study was conducted across 12 military dental centres using self‐administered questionnaire comprising demographical data, DC/TMD symptom questionnaire, OHIP‐14 and DASS‐21. A total of 3028 personnel, aged between 18‐65 years old, were invited to participate with an acceptance rate of 90.5%. Data analysis was done using non‐parametric tests, regression analysis and Spearman correlation ( P < 0.05). Results: Out of 2043 subjects (1998 males; 45 females, mean age 24.18 ± 7.18 years), 36.32% (n = 742) reported at least one TMD symptom. Significant differences in summary OHIP‐14, depression, anxiety and stress scores were observed between subjects with and without TMD symptoms. Significant differences in OHIP‐14 and DASS‐21 scores were observed between dissimilar type and number of TMD symptoms in the TMD group. Those with headaches and 2‐3 symptoms have substantially poorer OHRQoL and greater psychological distress. Associations between number of TMD symptoms, quality of life, depression, anxiety and stress were significant but weak ( r = 0.19‐0.40). Conclusions: Symptoms of Temporomandibular Disorders were prevalent among Asian military population. Significant differences in OHRQoL and psychological states were observed between subjects with and without TMD symptoms. Specific type and number of TMD symptoms impacted OHRQoL and psychological states differently. Associations between number of TMD symptoms and quality of life, depression, anxiety and stress were significant but weak.